2023
DOI: 10.1098/rstb.2022.0112
|View full text |Cite
|
Sign up to set email alerts
|

Can convergence in mixed-species flocks lead to evolutionary divergence? Evidence for and methods to test this hypothesis

Abstract: One of the most fundamental goals of modern biology is to achieve a deep understanding of the origin and maintenance of biodiversity. It has been observed that in some mixed-species animal societies, there appears to be a drive towards some degree of phenotypic trait matching, such as similar coloration or patterning. Here we build on these observations and hypothesize that selection in mixed-species animal societies, such as mixed-species bird flocks, may drive diversification, potentially leading to speciati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…From the empirical perspective, there have been many instances where birds that participate in MSFs have been hypothesized to look similar to each other; a previous study showed that for the majority of these cases, the birds do look more similar to each other than closely related species or others in the same habitat, at least to human eyes [ 26 ]. A recent article [ 27 ] has also hypothesized that plumage convergences in MSFs could even lead to speciation, if there are flock types in different areas that have distinct plumage colours (such as ‘yellow belly’ or ‘rufous-white’ flocks [ 28 ]) and then different populations of the same species come to resemble these different flock types. Nonetheless, it remains unclear whether flock-associated mimicry is a separate phenomenon from ISDM, or is closely connected to it.…”
Section: Introductionmentioning
confidence: 99%
“…From the empirical perspective, there have been many instances where birds that participate in MSFs have been hypothesized to look similar to each other; a previous study showed that for the majority of these cases, the birds do look more similar to each other than closely related species or others in the same habitat, at least to human eyes [ 26 ]. A recent article [ 27 ] has also hypothesized that plumage convergences in MSFs could even lead to speciation, if there are flock types in different areas that have distinct plumage colours (such as ‘yellow belly’ or ‘rufous-white’ flocks [ 28 ]) and then different populations of the same species come to resemble these different flock types. Nonetheless, it remains unclear whether flock-associated mimicry is a separate phenomenon from ISDM, or is closely connected to it.…”
Section: Introductionmentioning
confidence: 99%